Forced migration of chadians in the faro division in northern Cameroon (1980-2010) - Gormo, Jean (2013)
Since independence, there have been successive skirmishes in Africa, especially the Biafra war in Nigeria from 1967 to 1970, the sidelining of opponents to the regime of Sékou Touré in Guinea and the war of liberation in Guinea Bissau. Chad is not exempted from this. In fact, the political history of Chad from 1920 to 1990 is characterised by repeated violence, and coups d’état. Since the end of the seventies till the dawn of the 21st century, Chad has witnessed and still witnesses permanent instability. These various conflicts have led to great human loss and the displacement of hundreds of thousands refugees. Cameroon, which shares a border with Chad, is politically stable and acts as a host land for Chadian refugees. The acceptation or introduction of a new member into a society has always raised controversies. This is why the coming of Chadian refuges to the Faro Division has given birth to some changes whose effects are now visible. A question then comes to mind as to how the settlement of Chadian refugees in this area can be considered as an explicative variable of economic, socio-cultural and political dynamics in the division.